A Randomized Preference Trial Comparing Cognitive-Behavioral Therapy and Yoga for the Treatment of Late-Life Worry: Examination of Impact on Depression, Generalized Anxiety, Fatigue, Pain, Social Participation, and Physical Function. (7th May 2022) - Danhauer, Suzanne C.; Miller, Michael E.; Divers, Jasmin; Anderson, Andrea; Hargis, Gena; Brenes, Gretchen A.
Background: Depression, generalized anxiety, fatigue, diminished physical function, reduced social participation, and pain are common for many older adults and negatively impact quality of life. The purpose of the overall trial was to compare the effects of cognitive-behavioral therapy (CBT) and yoga on late-life worry, anxiety, and sleep; and examine preference and selection effects on these outcomes. Objective: The present analyses compared effects of the 2 interventions on additional outcomes (depressive symptoms, generalized anxiety symptoms, fatigue, pain interference/intensity, physical function, social participation); and examined whether there are preference and selection effects for these treatments. Methods: A randomized preference trial of CBT and yoga was conducted in adults ≥60 years who scored ≥26 on the Penn State Worry Questionnaire-Abbreviated (PSWQ-A), recruited from outpatient medical clinics, mailings, and advertisements. Cognitive-behavioral therapy consisted of 10 weekly telephone sessions. Yoga consisted of 20 bi-weekly group yoga classes. Participants were randomized to(1): a randomized controlled trial (RCT) of CBT or yoga (n = 250); or (2) a preference trial in which they selected their treatment (CBT or yoga; n = 250). Outcomes were measured at baseline and post-intervention. Results: Within the RCT, there were significant between-group differences for both pain interference and intensity. The pain interference score improved more for the CBT group compared with the yoga group [intervention effect of (mean (95% CI) = 2.5 (.5, 4.6), P = .02]. For the pain intensity score, the intervention effect also favored CBT over yoga [.7 (.2, 1.3), P < .01]. Depressive symptoms, generalized anxiety, and fatigue showed clinically meaningful within-group changes in both groups. There were no changes in or difference between physical function or social participation for either group. No preference or selection effects were found. Conclusion: Both CBT and yoga may be useful for older adults for improving psychological symptoms and fatigue. Cognitive-behavioral therapy may offer even greater benefit than yoga for decreasing pain.